Turkish Cypriot paternal lineages bear an autochthonous character and closest resemblance to those from neighbouring Near Eastern populations - Cemal Gurkan; Huseyin Sevay; Damla Kanliada Demirdov; Sinem Hossoz; Deren Ceker; Kerem Teralı; Ayla Sevim Erol (Taylor & Francis Group, 2017)
Background: Cyprus is an island in the Eastern Mediterranean Sea with a documented history of human settlements dating back over 10,000 years. Aim: To investigate the paternal lineages of a representative population from Cyprus in the context of the larger Near Eastern/Southeastern European genetic landscape. Subjects and methods: Three hundred and eighty samples from the second most populous ethnic group in Cyprus (Turkish Cypriots) were analysed at 17 Y-chromosomal short tandem repeat (Y-STR) loci. Results: A haplotype diversity of 0.9991 was observed, along with a number of allelic variants, multi-allelic patterns and a most frequent haplotype that have not previously been reported elsewhere. Pairwise genetic distance comparisons of the Turkish Cypriot Y-STR dataset and Y-chromosomal haplogroup distribution with those from Near East/Southeastern Europe both suggested a closer genetic connection with the Near Eastern populations. Median-joining network analyses of the most frequent haplogroups also revealed some evidence towards in situ radiation. Conclusion: Turkish Cypriot paternal lineages seem to bear an autochthonous character and closest genetic connection with the neighbouring Near Eastern populations. These observations are further underscored by the fact that the haplogroups associated with the spread of Neolithic Agricultural Revolution from the Fertile Crescent (E1b1b/J1/J2/G2a) dominate (>70%) the Turkish Cypriot haplogroup distribution.